Emporium. Issue 1 (1st April 2019) - Mort, Graham
In this short story, a man drifts into a bric-a-brac shop in a rural town to find the past confronting him. He is snared into a lie about his dead wife that haunts the story with images of the past and with actions that draw him deeper into an unintended act of deception.